Congenital hypopituitarism and multiple midline defects in a newborn with non-familial Cat Eye syndrome - Gregorio Serra; Clara Giambrone; Vincenzo Antona; Francesca Cardella; Maurizio Carta; Marcello Cimador; Giovanni Corsello; Mario Giuffrè; Vincenzo Insinga; Maria Cristina Maggio; Marco Pensabene; Ingrid Anne Mandy Schierz; et al. (Italian Journal of Pediatrics, 2022)
Abstract Background Cat eye syndrome (CES) is a rare chromosomal disease, with estimated incidence of about 1 in 100,000 live newborns. The classic triad of iris coloboma, anorectal malformations, and auricular abnormalities is present in 40% of patients, and other congenital defects may also be observed. The typical associated cytogenetic anomaly relies on an extra chromosome, derived from an inverted duplication of short arm and proximal long arm of chromosome 22, resulting in partial trisomy or tetrasomy of such regions (inv dup 22pter-22q11.2). Case presentation We report on a full-term newborn, referred to us soon after birth. Physical examination showed facial dysmorphisms, including hypertelorism, down slanted palpebral fissures, and dysplastic ears with tragus hypoplasia and pre-auricular pit. Ophthalmologic evaluation and heart ultrasound identified left chorioretinal and iris coloboma and ostium secundum type atrial septal defect, respectively. Based on the suspicion of cat eye syndrome, a standard karyotype analysis was performed, and detected an extra small marker chromosome confirming the CES diagnosis. The chromosomal abnormality was then defined by array comparative genome hybridization (a-CGH, performed also in the parents), which identified the size of the rearrangement (3 Mb), and its de novo occurrence. Postnatally, our newborn presented with persistent hypoglycemia and cholestatic jaundice. Endocrine tests revealed congenital hypothyroidism, cortisol and growth hormone (GH) deficiencies, which were treated with replacement therapies (levotiroxine and hydrocortisone). Brain magnetic resonance imaging, later performed, showed aplasia of the anterior pituitary gland, agenesis of the stalk and ectopic neurohypophysis, confirming the congenital hypopituitarism diagnosis. She was discharged at 2 months of age, and included in a multidisciplinary follow-up. She currently is 7 months old and shows a severe global growth failure, and developmental delay. She started GH replacement treatment, and continues oral hydrocortisone, along with ursodeoxycholic acid and levothyroxine, allowing an adequate control of glycemic and thyroid profiles as well as of cholestasis. Conclusions CES phenotypic spectrum is wide and highly variable. Our report highlights how among the possible associated endocrine disorders, congenital hypopituitarism may occur, leading to persistent hypoglycemia and cholestasis. These patients should be promptly assessed for complete hormonal evaluations, in addition to major malformations and midline anomalies. Early recognition of such defects is necessary to decrease fatal events, as well as short and long-term related adverse outcomes.